2019
DOI: 10.1080/12298093.2019.1620975
|View full text |Cite
|
Sign up to set email alerts
|

AcuDGene Knockout Attenuates the Virulence ofTalaromyces marneffeiin a Zebrafish Model

Abstract: Talaromyces marneffei is the only dimorphic species in its genus and causes a fatal systemic mycosis named talaromycosis. Our previous study indicated that knockdown of AcuD gene (encodes isocitrate lyase of glyoxylate bypass) of T. marneffei by RNA interference approach attenuated the virulence of T. marneffei, while the virulence of the AcuD knockout strains was not studied. In this study, T. marneffei-zebrafish infection model was successfully established through hindbrain microinjection with different amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…More than that, with the increased use of immunosuppressants such as anti-IFN-γ in organ transplant rejection reactions and autoimmune diseases, the number of individuals with non-AIDS-related infection caused by TM is on the rise ( Chan et al, 2016 ; Yu et al, 2018 ). Some specific pathogenic factors have been demonstrated in TM infection so far ( Cánovas and Andrianopoulos, 2006 ; Pongpom et al, 2013 ; Sapmak et al, 2016 ; Lau et al, 2018 ; Feng et al, 2019 , 2020 ). For example, cell wall mannoprotein 1 (MP1p) has been recognized as a key pathogenesis-related protein of TM in the infection process ( Sze et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…More than that, with the increased use of immunosuppressants such as anti-IFN-γ in organ transplant rejection reactions and autoimmune diseases, the number of individuals with non-AIDS-related infection caused by TM is on the rise ( Chan et al, 2016 ; Yu et al, 2018 ). Some specific pathogenic factors have been demonstrated in TM infection so far ( Cánovas and Andrianopoulos, 2006 ; Pongpom et al, 2013 ; Sapmak et al, 2016 ; Lau et al, 2018 ; Feng et al, 2019 , 2020 ). For example, cell wall mannoprotein 1 (MP1p) has been recognized as a key pathogenesis-related protein of TM in the infection process ( Sze et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As glucose amounts can be limited in certain body sites, many fungal pathogens can assimilate to non-glucose substrates, which can be metabolized via gluconeogenesis and the glyoxylate cycle to generate hexose and pentose sugars [ 75 , 76 ]. The disruption of carbon metabolic functions can impair the growth and virulence of fungal pathogens, emphasizing the essential role of central carbon metabolism in fungal pathogenicity [ 75 , 77 ]. Importantly, the enzymes involved in glycolysis, gluconeogenesis, the electron transport chain, and the glyoxylate and TCA cycles have been identified as antigenic proteins in A. fumigatus [ 52 ], C. albicans [ 54 , 69 , 78 ], C. parapsilosis [ 56 ], C. posadasii [ 60 ], C. gattii [ 57 ], C. neoformans [ 58 ], H. capsulatum [ 61 ], Paracoccidioides spp.…”
Section: Current Progress In the Identification Of Fungal Antigenic P...mentioning
confidence: 99%
“…Zebrafish neutrophils, also known as heterophils, respond to infection and injury in a manner that is similar to human neutrophils. For example, zebrafish neutrophils have been shown to migrate to the sites of bacterial (16), fungal (17)(18)(19)(20)(21)(22)(23), and viral (8,24,25) infections. Additionally, wounding studies have demonstrated neutrophil migration to the site of injury in zebrafish (26).…”
Section: Neutrophilsmentioning
confidence: 99%